2022
DOI: 10.3390/ijms232314510
|View full text |Cite
|
Sign up to set email alerts
|

Zfra Inhibits the TRAPPC6AΔ-Initiated Pathway of Neurodegeneration

Abstract: When WWOX is downregulated in middle age, aggregation of a protein cascade, including TRAPPC6AΔ (TPC6AΔ), TIAF1, and SH3GLB2, may start to occur, and the event lasts more than 30 years, which results in amyloid precursor protein (APP) degradation, amyloid beta (Aβ) generation, and neurodegeneration, as shown in Alzheimer’s disease (AD). Here, by treating neuroblastoma SK-N-SH cells with neurotoxin MPP+, upregulation and aggregation of TPC6AΔ, along with aggregation of TIAF1, SH3GLB2, Aβ, and tau, occurred. MPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…WWOX overexpression binds JAK2 and suppresses STAT3 phosphorylation (9). WWOX not only restricts cancer progression but also limits neurodegeneration (10)(11)(12)(13). WWOX gene deficiency induces neural diseases, metabolic disorders and early death in newborn infants (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WWOX overexpression binds JAK2 and suppresses STAT3 phosphorylation (9). WWOX not only restricts cancer progression but also limits neurodegeneration (10)(11)(12)(13). WWOX gene deficiency induces neural diseases, metabolic disorders and early death in newborn infants (11).…”
Section: Discussionmentioning
confidence: 99%
“…Whether and how the JAK1/STAT3 pathway participates in the neurodegenerative event and early death remains to be established. Downregulation of WWOX protein in the hippocampus and cortex in the mid-aged humans may lead to Alzheimer's disease during old age, which is due in part to aggregation of initiator proteins such as TRAPPC6AD, TIAF1 and SH3GLB2 (10,12,13). While STAT3 is also involved in neurodegeneration (2), we assume that downregulation of WWOX leads to aggregation of JAK1 or JKA2 that allows STAT3 to exert unwanted events in neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…92,93 TIAF1 aggregates with WWOX and p53 tumor suppressors may play differential roles in cancer pathogenesis and neural regeneration including Alzheimer's and Parkinson's disease. [94][95][96][97][98][99][100] The ability of MYO18A to convey migratory signals to the nucleus in three-dimensional matrix may sustain the invasion of malignant cells. 23 Considering these findings, the translational, mechanistic, and diagnostic role of MYO18A at the interface of cancer progression and neural degeneration must still be fully demonstrated.…”
Section: Roles In Immune Cells Of the Lymphoid Lineagementioning
confidence: 99%
“…We reported that when endogenous WWOX strongly binds intracellular protein partners in cancer cells, the cells cannot grow effectively in vivo [ 68 ]. When mice or cells are stimulated with the Zfra4-10 peptide, this peptide binds cell membrane hyaluronidase type II (Hyal-2) to activate the Hyal-2/WWOX/Smad4 signaling pathway [ 56 , 69 , 70 , 71 , 72 , 73 , 74 ]. The signaling activation leads to Smad4-mediated cell death or survival [ 69 , 70 , 71 , 72 , 73 , 74 ], cancer suppression [ 70 , 71 , 73 , 74 ], and restoration of memory loss in AD [ 71 ], depending upon the strength of signal activation.…”
Section: Zfra4-10 Activates Hyal-2/wwox/smad4 Signaling Pathway For R...mentioning
confidence: 99%
“…Zfra4-10-mediated restoration of memory loss in triple transgenic mice for AD (3xTg) occurs via its inhibition of the aggregation of amyloid beta 42 (Aβ42), accelerating the degradation of aggregated proteins and blocking the activation of inflammatory NF-κB [ 71 ] ( Figure 3 ). Zfra4-10 prevents the age-dependent progression of AD-like symptoms in 3xTg mice [ 72 ]. Whether Zfra4-10 suppresses the expansion of inflammatory glial cells in the brain is unknown.…”
Section: Zfra4-10 Activates Hyal-2/wwox/smad4 Signaling Pathway For R...mentioning
confidence: 99%